Expression of chalcone synthase and chalcone isomerase from Polygonum minus huds. in Escherichia coli, gene characterization, and structure elucidation of chalcone isomerase - Azman Shah, Fatin Lyana (2020)
Flavonoids are commonly found in plants and possessed vast benefits particularly towards the improvement of human health. These compounds that are attracting scientific attention, have been traditionally extracted from plant sources and synthesized chemically. Nevertheless, methods such as heat reflux and Soxhlet extractions are commercially infeasible, laborious, waste plant sources, and are environmentally unsafe due to the use of toxic solvents. Polygonum minus Huds. is a household-plant with flavonoids as one of its major compounds, hence engineering a plant’s phenylpropanoid pathway into microbial hosts for flavonoid production is an option, where these metabolites are produced without facing the issues mentioned. This study aims to identify and isolate chalcone isomerase (CHI) from P. minus, to express chalcone synthase (CHS) and CHI in Escherichia coli, and to predict the threedimensional (3D) structure of CHI protein from P. minus. The Open Reading Frame (ORF) of CHI gene was isolated through PCR amplification from P. minus cDNA. Various bioinformatics analyses were carried out to analyze the identified PmCHI protein sequence. Then, CHS and CHI genes from P. minus were codonoptimized, synthesized, and individually cloned into an expression vector. The recombinant vectors were later transformed into E. coli BL21(DE3). Temperature differences applied during the growth of recombinant E. coli BL21(DE3) expressing these enzymes were investigated, followed by western blot analysis and partial purification of these enzymes. As the 3D structure of PmCHS was predicted previously, Yet Another Scientific Artificial Reality Application (YASARA) software was used to construct the PmCHI model by using the CHI protein model of Deschampsia antartica Desv. (PDB ID: 5YX4) as template. The predicted model was analyzed, and previously theorized active site residues were highlighted. Then, the predicted model was validated by using validation programs and servers available online. ORF of PmCHI was identified to be ~700-bp long, encoding for 236 amino acid residues, with a predicted molecular weight of 25.4 kDa. Conserved residues involved in the active site cleft of CHI enzyme group are present in PmCHI protein sequence and was identified to belong to the class of Type I of CHI. PmCHI also comprises of more than 50% hydrophobic residues, lacks any signal peptide and transmembrane helices. The expression of CHS and CHI were observed at 16 °C and succeeding partial purification showed the potentials of these proteins to be fully purified for enzyme characterization studies. The Ramachandran plot showed that 93.9% of residues in the predicted PmCHI model were present in the most favored regions. Likewise, Verify3D and ERRAT showed that the 3D model of PmCHI gave values that are within the acceptable range of a good structure. As a conclusion, this study would provide more information on PmCHI and PmCHS enzymes, that can be incorporated into the flavonoid-producing pathway and engineered into a recombinant host, where significant yields of flavonoid compounds are expected.